중국소비자의 한국자동차 구매의도에 관한 연구 - 송운도(Yun-Tao SONG); 이종호(Jong-Ho LEE) (International journal of industrial distribution and business, 2019)
Purpose - This study intends to analyze Chinese consumers' purchase intention of Korean automobile. The aims of this study investigated to find out how product attributes and brand image affect the consumer's purchase intention of Korean automobiles in China. We consider the product attributes, brand image as evaluation criteria, also recognized as objectives for purchase intention. This study aims to analyze the positive effects on Chinese consumers' purchase intention with the variables by using the research model. Research design, data, and methodology - Based on theory of Purchase Intention, the concept of purchase intention was assessed by two factors: a) product attributes, and b) brand image to test the proposed hypotheses. The survey was conducted for 30 days, from October 17 to November 16 in 2018. With IBM SPSS Statistics 23.0 and IBM SPSS AMOS 23.0, factor analysis and regression, Cronbach's alpha and correlation were tested. 300 samples were used for this analysis. Results - As a main result, product attributes and brand image exerted significant effects on consumer's purchase intention. Thus, and were supported. The results showed that the product attributes, brand image had positive effects on purchase intention. The findings of this thesis are as follows: Firstly, automobiles' quality factors were divided into two categories like product properties (price, performance, design, economy, and safety), and brand image (awareness, favorability, reliability, and familiarity). Second, it showed that product properties and brand image had positive impacts on purchase intention of consumer. Conclusions - The impact of product attributes and brand image on consumer perceived value of Korean automobiles in China can be seen as a universal psychology of consumers who trust automobile products such as high quality, technology, ets. The results offer some insights into the extended model and have important managerial implications for Korean automobile enterprise. As the findings of this thesis show, all strategic orientations have significant and positive effects on the ability of innovation. At the same time, automobile company must pay attention to quality. As the relationship between the automobiles' performance and brand image were positive and significant, automobile companies should have comprehensive strategic orientations focused on strengthening these factors.